Binational survey of personal protective equipment (PPE) pollution driven by the COVID-19 pandemic in coastal environments: Abundance, distribution, and analytical characterization - De-la-Torre, G.E.; Dioses-Salinas, D.C.; Pizarro-Ortega, C.I.; Fernández-Severini, M.D.; Forero López, A.D.; Mansilla, R.; Ayala, F.; Castillo, L.M.J.; Castillo-Paico, E.; Torres, D.A.; Mendoza-Castilla, L.M.; Meza-Chuquizuta, C.; et al. (Elsevier, 2022)
In the present contribution, two nationwide surveys of personal protective equipment (PPE) pollution were conducted in Peru and Argentina aiming to provide valuable information regarding the abundance and distribution of PPE in coastal sites. Additionally, PPE items were recovered from the environment and analyzed by Fourier transformed infrared (FTIR) spectroscopy, Scanning electron microscopy (SEM) with Energy dispersive X-ray (EDX), and X-ray diffraction (XRD), and compared to brand-new PPE in order to investigate the chemical and structural degradation of PPE in the environment. PPE density (PPE m−2) found in both countries were comparable to previous studies. FTIR analysis revealed multiple polymer types comprising common PPE, mainly polypropylene, polyamide, polyethylene terephthalate, and polyester. SEM micrographs showed clear weathering signs, such as cracks, cavities, and rough surfaces in face masks and gloves. EDX elemental mapping revealed the presence of elemental additives, such as Ca in gloves and face masks and AgNPs as an antimicrobial agent. Other metals found on the surface of PPE were Mo, P, Ti, and Zn. XRD patterns displayed a notorious decrease in the crystallinity of polypropylene face masks, which could alter its interaction with external contaminants and stability. The next steps in this line of research were discussed.
Keywords: Mask; Plastic; Microplastic; Marine; SARS-CoV-2; https://purl.org/pe-repo/ocde/ford#3.03.05